Detox Fashion Supply Chain - Muthu, Subramanian Senthilkannan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This first volume on detox fashion discusses various interesting topics including a Toxic-Free Supply Chain for Textiles and Clothing; Environmental Issues in Textiles; Global Regulations, Restrictions & Research; Making the Change: Consumer Adoption of Sustainable Fashion; and Strategies for Detoxing Your Wardrobe. It provides an overview of the chemical-related issues confronting the fashion sector, summarizes global regulations, and discusses how to make the change by changing consumers' attitude towards adopting sustainable fashion, as well as the best strategies for detoxing our wardrobes.
1.Toxic Free Supply Chain for Textiles and Clothing -- 2. Detoxifying luxury and fashion industry: Case of market driving brands -- 3.Integrating Sustainable Strategies in Fashion Design by Detox 2020 plan - Case studies from Different Brands.
Keywords: Manufactures; Business logistics; Environmental chemistry; Industrial engineering; Production engineering; Chemistry, Technical; Machines, Tools, Processes; Supply Chain Management; Environmental Chemistry; Industrial and Production Engineering; Industrial Chemistry